From the ground up: a multidisciplinary approach to a phylogenetic and taxonomic revision of Embelia Burm.f. (Primulaceae - Myrsinoideae) - Dubéarnès, Anne (Trinity College Dublin. School of Natural Sciences. Discipline of Botany, 2021)
Embelia Burm.f. is a paleotropical genus of woody climbers belonging to the Myrsinoideae (Primulaceae), bearing punctate leaves, minute greenish-white or pale-yellow flowers, and small globose fruits. It is used as traditional medicine in its area of occurrence, and some of the compounds extracted from its leaves and fruits have been gaining attention in the pharmaceutical industry in recent years. Beyond its medicinal and cultural value, an accurate definition and understanding of Embelia is important, because its range overlaps with biodiversity hotspots and wilderness areas that undergo catastrophic decline. Its monograph was published in 1902, and its global taxonomy has not been revised since; its phylogenetic position in the Myrsinoideae is unknown and has never been studied using molecular methods. Because of a high level of morphological variability and the absence of recent revision, many of its species are poorly defined and difficult to identify. The objective of this thesis is to provide a revised taxonomic framework of Embelia by assessing its delimitation and position in the Myrsinoideae, refining its subgeneric structure, and re-evaluating the morphological characters that can be used for taxonomy. I start by analysing the taxonomic literature published on Embelia from the 17th century to the present day, and compile a list of all 142 currently accepted species. Based on the examination of herbarium material and on field observations conducted in Thailand, I then provide an updated description of Embelia, and clarify the definition of several important characters, notably habit, phyllotaxis, dioecy and inflorescence structure. I then assess the variability of floral morphology in three species, showing that significant intraspecific variation exists in almost all examined characters, that this variation is partially correlated with sexual dimorphism, and that some species are more variable than others. By providing the first description of pollen morphology in Embelia based on scanning electron microscopy, I show that pollen shape and texture can be useful for generic delimitation, but that pollen size is highly variable and must be used with caution. Using herbarium material and silica-dried leaf samples, the first molecular phylogeny of Embelia is then reconstructed, showing that Embelia is monophyletic but that it may be embedded within another Myrsinoideae genus, Cybianthus. It also shows that the subgeneric taxonomy of Embelia was partially inaccurate, and a revised taxonomy of the subgenera, including the description of a new subgenus and accompanied by updated morphological diagnostic characters, is presented. A taxonomic revision of the type subgenus in Malesia concludes this thesis, including the combination of Grenacheria into Embelia, the description of two new species and one subspecies, new synonymies, new combinations and lectotypifications.
APPROVED
Keywords: Plant taxonomy; Phylogeny; Primulaceae; Malesia; Plant morphology; Pollen morphology; Nomenclature; Systematics